2009
DOI: 10.1111/j.1365-2893.2009.01137.x
|View full text |Cite
|
Sign up to set email alerts
|

The disposition of hepatitis C antibody‐positive patients in an urban hospital

Abstract: Previous studies have indicated that only 26-61% of hepatitis C virus (HCV) antibody-positive patients are referred to specialists who treat HCV. However, these studies were conducted in homogeneous populations and before pegylated interferon and ribavirin became the standard of care for chronic HCV infection. The aims of this study were: (i) to determine the percentage of HCV antibody-positive patients who were referred to specialists for further management in an urban, racially diverse population, (ii) to de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…Similar to our prior studies and those of others, we found a high HCV detection rate of 15%. 5,6 While most infected patients had not yet been treated by the end of the first year of sofosbuvir availability, it is encouraging that over 10% of known cases were treated within 12 months of sofosbuvir approval, especially when this treatment initiation rate is compared to the interferon era.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar to our prior studies and those of others, we found a high HCV detection rate of 15%. 5,6 While most infected patients had not yet been treated by the end of the first year of sofosbuvir availability, it is encouraging that over 10% of known cases were treated within 12 months of sofosbuvir approval, especially when this treatment initiation rate is compared to the interferon era.…”
Section: Discussionmentioning
confidence: 99%
“…5,6 Until now, HCV treatment initiation and SVR have been rare events among urban patients. In a study including 293 HCV-infected patients at an urban Ohio county hospital, 28% (83) were treated and only 13% (11) of those treated achieved SVR.…”
mentioning
confidence: 99%
“…Our seropositivity of 16% is similar to other studies carried out in urban safety net hospitals. For example, a retrospective study performed at Metrohealth in Cleveland reported a 13% HCV seropositivity [ 13 ]. Such high proportions suggest that increasing testing rates at urban safety net hospitals could increase the number of patients who are aware of their HCV status in the United States.…”
Section: Discussionmentioning
confidence: 99%
“…Perhaps most importantly, the debilitating flu‐like symptoms and depression associated with interferon, and anaemia caused by ribavirin, contribute to treatment avoidance in eligible patients and adherence problems and discontinuation in many who are treated . In addition, an estimated 23% of newly diagnosed patients in the USA and 51% in the UK are not referred to a specialist after diagnosis , often because diagnosing physicians advise patients in early fibrosis stages to postpone treatment, hoping that more effective drugs will be developed before treatment is unavoidable .…”
Section: The Changing Hcv Treatment Landscapementioning
confidence: 99%